Unveiling genomic regions that underlie differences between Afec-Assaf sheep and its parental Awassi breed. Issue 1 (December 2017) - Seroussi, Eyal; Rosov, Alexander; Shirak, Andrey; Lam, Alon; Gootwine, Elisha
Abstract Background Sheep production in Israel has improved by crossing the fat-tailed local Awassi breed with the East Friesian and later, with the Booroola Merino breed, which led to the formation of the highly prolific Afec-Assaf strain. This strain differs from its parental Awassi breed in morphological traits such as tail and horn size, coat pigmentation and wool characteristics, as well as in production, reproductive and health traits. To identify major genes associated with the formation of the Afec-Assaf strain, we genotyped 41 Awassi and 141 Afec-Assaf sheep using the Illumina Ovine SNP50 BeadChip array, and analyzed the results with PLINK and EMMAX software. The detected variable genomic regions that differed between Awassi and Afec-Assaf sheep (variable genomic regions; VGR) were compared to selection signatures that were reported in 48 published genome-wide association studies in sheep. Because the Afec-Assaf strain, but not the Awassi breed, carries the Booroola mutation, association analysis ofBMPR1B used as the test gene was performed to evaluate the ability of this study to identify a VGR that includes such a major gene. Results Of the 20 detected VGR, 12 were novel to this study. A ~7-Mb VGR was identified onOvies aries chromosome OAR6 where the Booroola mutation is located. Similar to other studies, the most significant VGR was detected on OAR10, in a region that contains candidate genes affecting horn type (RXFP2 ), climate adaptation (ALOX5AP ), fiber diameter (KATNAl1 ), coat pigmentation (FRY ) and genes associated with fat distribution. The VGR on OAR2 includedBNC2, which is also involved in controlling coat pigmentation in sheep. Six other VGR contained genes that were shown to be involved in coat pigmentation by analyzing their mammalian orthologues. Genes associated with fat distribution in humans, includingGRB14 andCOBLL1, were located in additional VGR. Sequencing DNA from Awassi and Afec-Assaf individuals revealed non-synonymous mutations in some of these candidate genes. Conclusions Our results highlight VGR that differentiate the Awassi breed from the Afec-Assaf strain, some of which may include genes that confer an advantage to Afec-Assaf and Assaf over Awassi sheep with respect to intensive sheep production under Mediterranean conditions.